ChemInform Abstract: Platinum‐Catalyzed Cascade Rearrangement Reaction of 1, 5‐Diynyl Esters: Unusual Regioselective 1, 5‐Hydride Migration. Issue 52 (10th December 2015) - Zhu, Hui; Huang, Jiapian; Fan, Congbin; Chen, Zhiyuan
Abstract: Diynes of type (I), (III), and (V) are found to undergo a PtCl2 ‐catalyzed highly regioselective 1, 3‐acyloxy migration/pentannulation/1.5‐hydride shift process resulting in the formation of (E)‐2‐vinyl‐3‐oxo‐1‐methyleneindenes.